The Development of 2D Animation Video Application for Arabic Daily Conversations - Kalbun, Nor Asidah; Yasak, Zurina (Research and Innovation in Technical and Vocational Education and Training, 2024)
Arabic is often called the language of the Quran. It is considered one of the oldest languages in the world and develops according to current trends with various privileges and uniqueness, such as mediating the content of the Quran. This study was conducted for the development of a 2D animation video in Arabic (Daily Conversations) to provide exposure and basic knowledge about daily conversations to target users using the Android application platform. This daily conversation application (Arabic) has five parts, which are the application development introduction section, an animated video on the topic of saying hello, an animated video on the topic of self-introduction, an animated video on the topic of work and an animated video on the topic of time. The development of this animated video is interesting and suitable for the method of delivering information according to the current technological era, where individuals learn about daily conversations in Arabic through this 2D animated video. Meanwhile, the testing and evaluation of this 2D animation video were carried out by using expert verification checklist questions with three experts who were selected to carry out functionality testing and the design of this 2D animation video through vigorous expert testing. From the results of the study, all experts state that this 2D animation video can be used for learning Arabic communication. The paper concludes that 2D animated video can provide better and more interesting up-to-date exposure.